Measurement of the Effectiveness of Zakat Disbursement on Dompet Sosial Madani - Efri Syamsul Bahri; Abdullah Mubarok; Salsiati (International Journal of Management Science and Application, 2023)
Zakat is an obligation for Muslims who have fulfilled the haul and nishab requirements. Dompet Sosial Madani (DSM) is the entity that manages Zakat at the Bali Province level. This study aims to measure the effectiveness of Zakat distribution in DSM. This research was conducted using a quantitative method with a descriptive approach. The data is sourced from the DSM Financial Statements for 2017-2022. Measuring the effectiveness of distribution uses the formula allocation to collection ratio (ACR) approach. The results showed that the ACR value was 94 per cent. Thus, the level of effectiveness of Zakat distribution at DSM is in the Highly Effective category. DSM must maintain an effectiveness ratio above 90 per cent to optimize Zakat benefits for Mustahiq.